GIS Mapping of Water Quality Index for Sungai Benut, Simpang Renggam - Razak, Fathiah; Anjang Ahmad, Mustaffa (Recent Trends in Civil Engineering and Built Environment, 2023)
This study aimed to characterize the river pollution at Sungai Benut, Simpang Renggam by calculating the Water Quality Index (WQI) and use Geographic Information System (GIS) to get the detailed condition of the study area. 3 different WQI models were computed from 8 water samples that were collected for on-site testing and physiochemical analysis. Six parameters were considered in calculating the WQI such as Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Acidic and Alkaline(pH), Dissolved Oxygen (DO), Total Suspended Solids (TSS) and Ammonia Nitrogen (NH3). Then, the WQI’s variability thematic maps were created using QGIS software based on spatial and non-spatial database. As a result, 1 station was categorized as slightly polluted, 4 stations were classified as polluted and 3 stations were poorly polluted. These analysis indicated that GIS has the potential to efficiently present an interactive visualizations over a large study area in order for the authorities to upgrade the water quality management system